African Perceptions of Trade Partners: A Ghanaian and Togolese Perspective of Sino-African Relations. Issue 2 (July 2020) - Awoonor, Akorkor Kehinde; Forson, Joseph Ato
Studies on perception in both development studies and international relations have shown that most nations have mutual perceptions predicated on and influenced by either fact, biases or stereotypes, or a combination of other identifiable qualitative variables. In this study, we explore and demonstrate that African perceptions differ from country to country and are well influenced by factors such as the country of origin, the knowledge base and orientation towards China. The connection between Africa and China is long etched in history (206bce to 220ce ) evidenced by a series of cultural and trade exchanges between China and Egypt, and long since antiquated in historical records by the Chinese traveller, Du Huan, of the Tang Dynasty. With a combination of primary and secondary data collected via social survey using google forms with questionnaires administered to participants of 10 and 6 tertiary institutions in Ghana and Togo, respectively, and bolstered with documentary evidence, we find that there are no singular overarching African perceptions of China, as the African continent is a 55-state region with diverse conflicting political, economic and sociocultural proclivities. The study further observed that compared to Togolese, more Ghanaians perceive China to be a goodwill partner predicated on its involvement on public health emergencies of international concerns (PHEIC) and influence on national economies through debt reliefs and other form of assistance.